CBF VAR em midiatização (2018 -2022): a circulação como uma dimensão para a percepção das inovações no espetáculo esportivo - Silva, Pedro Vasconcelos Costa e (Universidade do Vale do Rio dos Sinos, 2022)
Based on mediatization studies, the goal of this research is to investigate how the innovation of CBF VAR (Brazilian Football Confederation Video Assistant Referee) has been received by social actors and institutions involved in the production and reception of the football spec-tacle in Brazil. On one hand, federations and tech companies responsible for VAR patent try to legitimize the implementation of the video assistant referee as a solution for old problems in football refereeing related. On the other hand, adoption process showed discrepancies between what is offered and what is produced while meanings that tension on circulation envi-ronment (FAUSTO NETO, 2010; 2016; 2018; 2020 and VERÓN, 1997; 2004; 2013; 2014). In contact zones (FAUSTO NETO, 2018) we seek to understand both what emerges as strat-egies and discursivities produced by the specialist assigned to observe VAR’s work in tradi-tional institutions of the media field (RODRIGUES, 2000) and digital networks. Field in which social actors in reception engage in many ways turning the communication ambience complex. We seek to observe the interpenetrations (LUHMANN, 2011; 2016) between the political field, sportive, economic and mediatic from the investigation of circulation of CBF VAR, meanings about the innovation that materialize in this work from the description of the arrangements that constitute an interactional device (BRAGA; 2011; 2020). Our work there-fore relies on a new interpretative effort of the dispositif. For our analyses we constituted a Mediatized Case in an attempt to capture innovation updates between 2018 and 2022. The process of collecting evidence and the selection of empirical materiality resulted in the choice of three occurrences that organize the Case. Circumstances related to the use of VAR in the football field that unfold in the media, allowing the perception of collateral issues that make us think about the game, about technology, about surveillance and about innovations in the mediatized society. In this sense, we try to describe and reflect a new way of playing the game, innovating and living in the world (GOMES, 2017).
Keywords: VAR; Circulação; Futebol midiatizado; Interpenetrações; Espetáculo esportivo; Circulation; Mediatized football; Interpenetrations; Sportive spectacle; ACCNPQ::Ciências Sociais Aplicadas::Comunicação